SSU rRNA reveals a sequential increase in shell complexity among the euglyphid testate amoebae (Rhizaria : Euglyphida) - Lara, Enrique; Heger, Thierry J; Mitchell, Edward; Meisterfeld, Ralf; Ekelund, Flemming (My University, 2007)
The existing data on the molecular phylogeny of filose testate amoebae from order Euglyphida has revealed contradictions between traditional morphological classification and SSU rRNA phylogeny and, moreover, the position of several important genera remained unknown. We therefore carried out a study aiming to fill several important gaps and better understand the relationships among the main euglyphid testate amoebae and the evolutionary steps that led to the present diversity at a higher level. We obtained new SSU rRNA sequences from five genera and seven species. This new phylogeny obtained shows that (1) the clade formed by species of genera Assulina and Placocista branches unambiguously at the base of the subclade of Euglyphida comprising all members of the family Trinematidae and genus Euglypha, (2) family Trinematidae (Trachelocorythion, Trinema, and Corythion) branches as a sister group to genus Euglypha, (3) three newly sequenced Euglypha species (E. cf. ciliata, E. penardi, and E. compressa) form a new clade within the genus. Since our results show that Assulina and Placocista do not belong to the Euglyphidae (unless the Trinematidae are also included in this family), we propose the creation of a new family named Assulinidae. Consequently, we give a family status to the genera Euglypha and (tentatively) Scutiglypha, which become the new family Euglyphidae. The evolutionary pattern suggested by SSU rRNA phylogeny shows a clear tendency towards increasing morphological complexity of the shell characterised by changes in the symmetry (migration of the aperture to a ventral position and/or compression of the shell) and the appearance of specialised scales at the aperture (in families Trinematidae and Euglyphidae). (C) 2007 Elsevier GmbH. All rights reserved.
Keywords: phylogeny; testate amoebae; protist; protozoa; evolution; morphology; ECOLOGY; EVOLUTIONARY; RHIZOPODA; SPHAGNUM; PROTOZOA; SUBSTITUTION; PEATLANDS; PROTISTS; LINEAGE; SOIL